Emerging anti-poverty infrastructural gaps in suburbia: Poverty and the voluntary sector across Metropolitan Sydney. (March 2021) - DeVerteuil, Geoff; Hartt, Maxwell; Potts, Ruth
Suburbs are subject to numerous stereotypes, including that they lack density, diversity and inclusivity. While these stereotypes have largely been dispelled, the deficit around anti-poverty infrastructure remains understudied. The focus of this paper is to systematically investigate the ostensible mismatch between (a) the emerging suburbanization of poverty, and (b) the potential lack of anti-poverty infrastructure to serve it, with a focus on suburban voluntary sector provision. These aims address the potential infrastructural deficit around voluntary sector provision in suburban areas of prosperous global cities in the Global North. Using Metropolitan Sydney as the case study, we investigate the extent of the suburban infrastructure service deficit across metropolitan space in 2016, comparing poverty patterns and supply of voluntary sector organizations. We find that poor inner and outer suburbs featured fewer services than the inner city, both per capita and per low-income residents, confirming an anti-poverty infrastructural gap.